Culex spp. Mosquito Larva Control by Appling Novaluron in Polluted Water - โรจน์ฤทัย, เสียงธรรมวิมล; กลั่นเรืองแสง, รุจิรา; อดิศัยมนตรี, สุวรรณ; สามัง, ยุทธนา; บุญจุน, บุณณ์ภัสสร; เลิศวิธี, ชุบ (Disease Control Journal, 2012)
The Culex spp. mosquito density in Sena municipality was still so high even the space spraying was carried out because mosquito breeding place, polluted water was abundant. The Office of Disease Prevention and Control 1, Bangkok applied Novaluron to control culex spp. mosquitoes larvae. After treated with 10 mg. (a.i.) Novaluron /m2 in polluted water, the 2nd- 4nd instar lavae and pupae were reduced to 5096 in 24 hours and inhibit of emergence effect was persisted for 4 weeks. Novaluron was an alternative method to control Culex spp. mosquitoes lavae. However, even through this substance was safe to mammals and environmental friendliness but it had an inhibit effect to chitin sheet development in some animals such as crabs, shrimps, water fleas and non-target immature stages of aguatic insects, etc